GROWTH PATTERNS OF CHILDREN UNDER FIVE IN URBAN SLUMS IN SAMBALPUR DISTRICT OF ODISHA - TRIPTI KUMARI, (The Journal of Research ANGRAU, 2025)
A community based cross sectional study was conducted in the years 2022-23 among under five children living in urban slums of Sambalpur district, Odisha. The proposed study aimed to  determine the levels of malnutrition among under-five children and to evaluate the growth of  these children by anthropometric measurements. A total sample size of 550 (268 boys and 282  girls) aged between 6 months to 5 years were randomly selected from 20 slums. The data was  collected with the help of a predesigned and pretested interview schedule to collect the information  on anthropometric measurements and nutritional status of the children. The results of the study  revealed that more percentage of actual mean deficits was found in Head Circumference (HC) &  Mid-Upper Arm Circumference (MUAC) of the boys. The nutritional status of girls was found to be  less in comparison with boys in Grade-I, Grade-II, Grade-III level of malnutrition, both according  to Gomez Classification and Indian Academy Pediatrics (IAP) classification.